ANALISIS MATERIAL REMOVAL RATE (MRR) BAJA SKD 11 PADA PROSES CNC TURNING DENGAN MENGGUNAKAN METODE TAGUCHI - Jekki Dodi Parlindungan Sihombing; Robert Napitupulu; Angga Sateria (Prosiding Seminar Nasional Inovasi Teknologi Terapan, 2022)
High MRR is a target to be achieved in the workpiece process using CNC turning. However, a slow process will affect the processing time of the product, and will increase production costs. To overcome this, it is necessary to set the right process parameters to produce the most influential contribution to the MRR and also to produce the maximum parameter value. The purpose of this research is to determine the effect of parameters (cutting speed, spindle speed and depth of cut) on the MRR and to determine the proper setting of process parameters in order to produce the maximum MRR for SKD-11 steel. The experimental design used is the L18 (21 x 37) orthogonal matrix. The repetition was done twice. From the results of the study, the MRR of the workpiece by using a combination variable setting that has the maximum value occurred in the 2nd combination experiment, with a value of 4.648 mm3/minute. With Spindle Rotation set at 210 put/min, feed depth set at 1.5 mm, feed motion set at 0.05 mm/rev.